TREATMENT FOR ORAL MUCOSAL CANCER - L. P. Yakovleva (Опухоли головы и шеи, 2015)
The literature review analyzes current trends in the treatment of oral mucosal cancer. Surgery performed at the first stage of complex or combination treatment, followed by radiation or platinum drug-based competitive chemotherapy, is the standard treatment. To choose treatment policy depends on the extent of a tumor process and the presence of unfavorable prognostic factors that determine the high risk of disease recurrence and progression. The basic principles of combination and complex therapy are to strictly comply with the time and sequence of therapy. The treatment of recurrent tumors to be surgically untreated is based on chemotherapy using platinum and target drugs.